EVALUASI AKUNTANSI PERTANGGUNGJAWABAN TERHADAP EFEKTIVITAS DAN EFISIENSI PENGENDALIAN MANAJEMEN (STUDI KASUS PADA SATUAN KERJA PENGEMBANGAN KINERJA PENGELOLAAN AIR MINUM BANGKA BELITUNG DINAS PEKERJAAN UMUM PROVINSI KEPULAUAN BANGKA BELITUNG ) - Anggraeni, Nining; Karmawan, - (Journal of Accountancy FE UBB, 2013)
The purpose of this study was to investigate and evaluate the concept of responsibility accounting which was applied in achieving effectiveness and efficiency of management control in the Satuan Kerja Pengembangan Kinerja Pengelolaan Air Minum Bangka Belitung. The research method used was descriptive method with qualitative literature study techniques and case studies. Analytical method used was comparing the theories held by the data obtained from case studies.From the research, Satuan Kerja Pengembangan Kinerja Pengelolaan Air Minum Bangka Belitung had used the accounting system of accountability and pplied consistently to achieve the effectiveness and efficiency of management control. It could be seen from the statement of responsibility accounting which was quite good to show increase of realization of the budget and on time job completion.Keywords :      Responsibility Accounting, Effectiveness And Efficiency,  Management Control